Analysis of the wind and wave-induced dynamic response of a floating offshore wind turbine integrating a compressed air energy storage system. Issue 5 (October 2020) - Farrugia, Daniel; Sant, Tonio; Buhagiar, Daniel; Farrugia, Robert N
In order to address the intermittency of offshore renewable energy sources, a novel form of compressed air energy storage integrated within a tension leg platform is proposed. The energy storage concept involves a hydro-pneumatic accumulator. The objective of this study was to investigate the variation in the physical and hydrodynamic characteristics of a hypothetical full-scale prototype of the proposed system. The design was developed so as to analyse the effect on said characteristics of the tension leg platform diameter and the inner diameter of the umbilical connecting the floating and seabed-mounted compressed air chambers. Results indicate that better hydrodynamic behaviour was observed for smaller diameter tension leg platforms, whereby the resulting motion became more restrained. Moreover, the dynamic characteristics were observed to indicate marginal improvement for increasing inner diameters of the pneumatic umbilical.